Identification of loci governing soybean seed protein content via genome-wide association study and selective signature analyses - Zhang, Hongmei; Zhang, Guwen; Zhang, Wei; Wang, Qiong; Xu, Wenjing; Liu, Xiaoqing; Cui, Xiaoyan; Chen, Xin; Chen, Huatao (Frontiers in Plant Science, 2022)
Soybean [Glycine max (L.) Merr.] is an excellent source of protein. Understanding the genetic basis of protein content (PC) will accelerate breeding efforts to increase soybean quality. In the present study, a genome-wide association study (GWAS) was applied to detect quantitative trait loci (QTL) for PC in soybean using 264 re-sequenced soybean accessions and a high-quality single nucleotide polymorphism (SNP) map. Eleven QTL were identified as associated with PC. The QTL qPC-14 was detected by GWAS in both environments and was shown to have undergone strong selection during soybean improvement. Fifteen candidate genes were identified in qPC-14, and three candidate genes showed differential expression between a high-PC and a low-PC variety during the seed development stage. The QTL identified here will be of significant use in molecular breeding efforts, and the candidate genes will play essential roles in exploring the mechanisms of protein biosynthesis.